Sinsai Roo Jai Ton: Relearn through training life-skill in the process of making puppet performance for self -Understanding - Jantaharn, Ratchaneekorn (Journal of Fine and Applied Arts Khon Kaen University, 2022)
Sinsai Roo Jai Ton: Relearn through training life-skill in the process of making puppet performance for self -understanding. In the article, the author reflects on the notes and analyzes the views of the authors who have played a part. One of the participants throughout the process of the Sinsai understanding, Research Project in the process of creating a contemporary puppet. Throughout the period of 2 years during 2016-2018, I were worked with the research project leader, Pachaya Akkapram, and 6 participants in the project, who were first year students at that time, including the authors. They can divide the practice and learn sessions by themselves through practice and doing 3 main phases: Phase 1, Mind Test, phase 2, Creative Circle, and phase 3Sinsai Dern Dong. In each phase, the author participated in the process of practicing life skills and creating contemporary puppets and working with community artists, Teacher Siang PreechaKarun, Father, Mother, Teacher, Grandpa, and Grandma in the village,Which is a collaboration for many ages so, help fill in the gaps of the distant age, moving closer to each other.